Student engagement in learning: a preliminary study on digital educational application - Suhaila Jaffar; Dinna @ Nina Mohd Nizam; Aslina Baharum; Nooralisa Mohd Tuah; Farhana Diana Deris; Noorsidi Aizuddin Mat Noor (UniSE Press, 2021)
In this modern age, more children are becoming frequent smartphone users. This research presents an approach to engage students with Digital Educational Games. The emergence of digital technologies has increased interest in education and the learning process. Particularly in e-learning, teachers face difficulties in promoting and engaging students in the learning process, and vice versa. However, thanks to new technology that incorporates new methods into the e-learning process overcomes these problems. The objectives of this study are to identify the features and guidelines for designing an engaging Digital Educational Games using qualitative method. A locally developed educational application was used in the preliminary study to identify the gamification elements on 15 participants, and seven elements were identified. A proposed guideline to encourage learning engagement from this study and literature review was suggested. This research shows gamification, which by hope future research can develop educational games that engages students to learn.